The Community Experiences of Social Assistance Programmes Following a Disaster in Indonesia: 2010 Mount Merapi Eruption - Hernanto, Henrikus Adi (Auckland University of Technology, 2016)
Social assistance programmes have been noted as one of the important keys to determining the success of the recovery process in the aftermath a disaster. It has also been shown that social assistance programmes following a disaster, significantly contribute to the recovery phase of disaster management, by utilizing the communities? capacity to facilitate community recovery from a disaster. Through the community recovery framework, social assistance programmes, with active collaboration and interaction between the community and the social assistants, can speed up community recovery efforts; contributing to the disaster recovery management. The Law of the Republic of Indonesia Number 11 of 2009 and Regulation of the Ministry of Social of the Republic of Indonesia Number 82 of 2006 set out and guide the social assistance delivery to the community. However, most of the literature addressing social assistance programmes, following a disaster in Indonesia, is from the government?s perspective, the legislation outlook and the social assistants? point of view. Little is known about the benefit and practice of the social assistance programmes from the perspectives of the affected community. Therefore, the current study sought to address this gap by exploring the experiences of social assistance within the affected community following a disaster. With this knowledge, the government, NGOs, private sectors and other parties would gain insights, inputs and recommendations from the affected community, to whom the programmes were delivered, so that social assistance programmes following a disaster may be made more effective. A qualitative study was conducted in Kinahrejo hamlet, the most affected community from the 2010 Mount Merapi eruption. Data was analysed using qualitative descriptive methodology via open-ended and close-ended questions with 10 participants. The study explored whether the lived experiences of the Kinahrejo community was congruent with Indonesian regulation regarding social assistance programmes. This study has contributed to the field of research on social assistance programmes following a disaster by providing findings on the importance of the mentioned programmes toward the affected community from the community?s experiences and perspectives.
Keywords: Community experiences; Social assistance programmes; 2010 Mount Merapi; Emergency management